Research of steel E – class weldability - Kostin, A.; Martynenko, V.; Labartkava, A. (My University, 2016)
The purpose of this research is to compare of steel E rolled sheet analytical and experimental methods of weldability assessment. The mathematical models, designed by Paton Institute and based on the analysis of the literature data and the research of about 150 diagrams of austenite thermokinetics decay, were used for the calculation. The analysis of the received results has showed that the analytical methods of the calculation of the mechanical characteristics of heataffected zone (HAZ) high temperature parts by use of the chemical content, taking into account the speed of the welded junctions cooling, give the high level of reliability (at temperature which are above zero) and can be used for the original assessment of the metal peculiarities of HAZ steel E rolled sheet junctions of big thickness. The analytical assessment of the impact effect does not provide the reliable result. It is connected with that the range of the real values has the error in each zone of the welded junction at limits 30 ÷ 500 %. It reduces the correlation coefficient of the received results. It makes impossible the accurate prediction of HAZ metal impact effect values.
Kostin, A. Research of steel E – class weldability / A. Kostin, V. Martynenko, A. Labartkava // WORKS OF GTU. – TBILISI: Publishing House “Technical University”, 2016. – № 4 (502). – С. 102–109.
Keywords: analytical methods of calculation; impact strength; hardness; mechanical characteristics; steel E-class; weldability assessment